Seed attributes, germination responses and seedling growth of silk cotton tree Bombax ceiba L. - Niroula, Bhabindra; Pokhrel, Dillli Ram; Jha, Sasinath (Nepalese Journal of Biosciences, 2013)
In vitro Seed germination through different treatments, and seedling growth of Bombax ceiba were studied from April 2009 to January 2010. Fifty seven per cent seed germination at control condition was enhanced up to 63% by continuous tap water washing for 48 h duration. Freshly collected seeds in April did not germinate in May and June. Stem diameter and height of one and 6 months old seedlings were 0.3 cm, 1.2 cm and 1.2 cm, 87.1 cm, respectively. DOI: http://dx.doi.org/10.3126/njbs.v2i0.7497 Nepalese Journal of Biosciences 2 : 109-112 (2012)